La Deuxième Internationale face à la question coopérative, 1889-1914 - Andrea Benedetti (Cahiers d’histoire)
The Second International (1889-1914) experiences difficulties in defining its relations with the cooperative movement, since the theoretical differences between its affiliated parties crystallize around three questions: should cooperatives be considered as a premise of the future socialist order? Should there be an organic unity or organizational autonomy between the party and the cooperatives? Do the national parties remain sovereign, or can the authorities of the International dictate to them a line of conduct in cooperative matters? If the first congresses neglected cooperativism, from 1900 the International Socialist Bureau, led by a team of Belgian socialist cooperators, adopts a gradual and pragmatic approach to strengthen the links between parties and cooperatives. The Copenhagen congress of 1910 finally deals with the cooperative question but has to adopt a balancing resolution which remains without a future.